Baker, Herbert (Sir). Glenshiel, Westcliff, Johannesburg- House for Col. W. Dalrymple. 1910. Ground floor plan; First floor plan; Plan of roof; Elevations (plans & sections) & Plan for stables- Parktown, Johannesburg. Ink on parchment. Jun 1910. - Baker, Herbert (Sir) (My University, 2012)
Baker, Herbert (Sir). Glenshiel, Westcliff, Johannesburg- House for Col. W. Dalrymple. 1910. Ground floor plan; First floor plan; Plan of roof; Elevations (plans & sections) & Plan for stables- Parktown, Johannesburg. Ink on parchment. Jun 1910.
Ink on parchment. Plans: 527X718. Stables: 525X710. Elevation: 630X1010
Keywords: Baker, Herbert (Sir). Glenshiel, Westcliff, Johannesburg- House for Col. W. Dalrymple. 1910. Ground floor plan; First floor plan; Plan of roof; Elevations (plans & sections) & Plan for stables- Parktown, Johannesburg. Ink on parchment. Jun 1910.